Tsunami Hazard A Practical Guide for Tsunami Hazard Reduction - Bernard, Eddie N. (Springer Netherlands, 1991)
The Fourteenth International Tsunami Symposium held from 31 July to 3 August 1989 in Novosibirsk, U.S.S.R., was sponsored by the International Union of Geodesy and Geophysics. Sixty-five scientists from 13 countries met to exchange information on recent advances in tsunami research. The Symposium was a great success due to the enthusiasm of the participants, the quality of research presented, and the great organization provided by the Soviet hosts. Teams of dedicated workers, under the fine leadership of Academician A. S. Alexseev and Dr V. K. Gusiakov, blended social and scientific activities in a memorable fashion. The 62 presentations of the Symposium were divided into six areas of research: generation (7), propagation (12), coastal effects (10), observations (11), seismics and tectonics (10), and hazard mitigation (12). A summary of the research presented appears as the first article in this special issue. Following the Symposium, a team of session chairmen nominated 20 of these oral presentations to be published in a special issue devoted to the International Tsunami Symposium